Conceptual project of a semi-autonomous vehicle for remote monitoring of environmental variables - Figueredo, Edel Mary Quinn de Oliveira; Marinho, George Santos (Companion Proceedings of the Brazilian Symposium of Robotics & Latin American Robotics Symposium (SBR/LARS); 2021: Companion Proceedings of the 13th Brazilian Symposium of Robotics & 18th Latin American Robotics SymposiumDO - 10.5753/wtdr_ctdr.2021.18680, 2021)
It presents the conception of a semi-autonomous vehicle for environmental exploration, designed to collect and transmit data on soil variables (moisture and salinity). The project was conceived considering a vehicle capable of moving in areas with potential for desertification, previously identified in satellite images, and helping to characterize environments through data intercomparison. It may also be part of a space system for localized collection, satellite transmission and data reception in a mission control center. From the explorations through the vehicle, the possibility of supporting projects of recovery and soil management, enabling It presents the conception of a semi-autonomous vehicle for environmental exploration, designed to collect and transmit data on soil variables (moisture and salinity). The project was conceived considering a vehicle capable of moving in areas with potential for desertification, previously identified in satellite images, and helping to characterize environments through data intercomparison. It may also be part of a space system for localized collection, satellite transmission and data reception in a mission control center. From the explorations through the vehicle, the possibility of supporting projects of recovery and soil management, enabling the sustainable use of the soil, is considered.